Wear-resistant hard alloy for tamping pickaxe and preparation method of wear-resistant hard alloy
By using cemented carbide composed of 75-95% WC and 5-25% Ni, Co, Mo, and Ru in the tamping pick, combined with a multi-layer composite structure with diamond coating, the wear resistance and resistance of the tamping pick are solved. The problem of insufficient impact ability significantly improves its mechanical strength and wear resistance.
Patent Information
- Application Number
- CN202411243010.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing tamping picks are insufficient in wear resistance and impact resistance during use, making it difficult to maintain effective performance under high-frequency vibration and friction conditions.
A wear-resistant cemented carbide is adopted, the alloy part consists of 75-95% WC hard phase and 5-25% Ni, Co, Mo, Ru and other bonded phases. By optimizing the particle size of WC and Ru particles The diameter distribution forms a diffuse substructure and a skeleton structure, combined with a multi-layer composite structure with diamond coating, to improve the mechanical strength and wear resistance of the alloy.
It significantly improves the mechanical strength and wear resistance of cemented carbide, reduces the generation of wear chips, improves the lubricating effect under stress, and extends the service life.
Smart Images

Figure CN119307798A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of tamping picks, and more specifically, to a wear-resistant hard alloy for tamping picks and a preparation method thereof. Background Art
[0002] The railway tamping pick is a key component of the railway tamping vehicle. During the operation of the tamping vehicle, the tamping pick is driven by a hydraulic device and inserted into the roadbed ballast. Through high-frequency vibration, the density of the ballast bed is increased and the stability of the track is improved. The xky-q-1 carbide tamping pick is an accessory for tamping vehicles such as DC-32, DCL-32, and DWL-48.
[0003] The tamping pick has to withstand a great impact force at the moment it is inserted into the ballast bed. During the vibration process, the ballast produces strong friction on the pick palm. Therefore, the tamping pick is required to have sufficient impact resistance and high wear resistance. Summary of the invention
[0004] In order to improve the wear resistance and impact resistance of a tamping pick, the present application provides a wear-resistant cemented carbide for a tamping pick and a preparation method thereof.
[0005] The present application provides a wear-resistant hard alloy for a tamping pick, which adopts the following technical solution:
[0006] In a first aspect, the present application provides a wear-resistant hard alloy for a tamping pick, comprising an alloy portion and a coating disposed outside the alloy portion, wherein the alloy portion comprises the following substances in parts by weight:
[0007] 75-95 parts of hard phase;
[0008] 5-25 parts of adhesive phase;
[0009] The hard phase includes WC;
[0010] The bonding phase includes any one or more of Ni, Co, Mo, and Ru; the particle size of Ru is 1-2 μm.
[0011] By adopting the above technical scheme, preferably Ni, Co, Mo, Ru are used as the bonding phase, W, C have good solubility in Co, can make cemented carbide have better mechanical properties, Ni and Co are elements of the same family, have high similarity, so the addition of Ni can dissolve W, C elements and can introduce antioxidant properties in cemented carbide, effectively enhance the corrosion resistance of cemented carbide in complex environment. The introduction of Mo element can act as a growth inhibitor WC grain growth, refine the grains in the alloy part, make the bonding phase uniformly distributed, thereby further enhancing the mechanical strength of the alloy part. The alloy with Mo added has less wear debris because of increased hardness, and under the action of stress, the wear debris forms a compacted layer between the alloy surface and the friction pair, which can play a lubricating role, thereby improving the wear resistance of the alloy part. The addition of Ru can accelerate the polycrystalline transformation of Co cubic crystal to hexagonal crystal, and then produce a dispersed substructure in the alloy part, slightly refine the WC grains, reduce the transgranular fracture of abnormally grown WC grains in the failure process, and effectively improve the wear resistance and mechanical strength of cemented carbide.
[0012] At the same time, the present application optimizes the particle size of Ru. At an appropriate particle size, Ru can be evenly distributed, evenly improving the dislocation strain energy of the alloy part, and increasing the solid solubility of Ru in Co, thereby increasing the dispersion of Ru, thereby enabling the cemented carbide to obtain better mechanical strength.
[0013] Optionally, the WC includes coarse-grained WC, medium-coarse-grained WC and ultrafine-grained WC.
[0014] By adopting the above technical solution, the present application optimizes the particle size of WC, selects coarse-grained WC, medium-coarse WC and ultrafine-grained WC as the hard phase, so that a grading effect can be formed in the hard phase, and the addition of medium-coarse WC and ultrafine-grained WC can alleviate the abnormal growth of grains and reduce the generation of ultra-coarse grains; the fine-grained WC and ultrafine-grained WC dissolved from the medium-coarse WC can move with the bonding phase and be evenly distributed around the coarse-grained WC, effectively improving the adjacency of the alloy; in addition, the introduction of medium-coarse WC is not prone to cracking and breaking, reduces the generation of micro-abrasive particles, and can also serve as a skeleton structure in the alloy part to improve the skeleton strength in the alloy part, while maintaining the strength of the alloy part, effectively improving the wear resistance of the alloy part.
[0015] Optionally, the WC includes coarse-grained WC, medium-coarse WC and ultrafine-grained WC in a mass ratio of 6-7:2-3:1.
[0016] By adopting the above technical solution, the addition amount of medium-coarse WC and ultrafine-grained WC is optimized. The appropriate addition amount of medium-coarse WC and ultrafine-grained WC can make the alloy part obtain uniform density, reduce the generation of micro-abrasive particles, and thus make the alloy part obtain suitable mechanical strength and wear resistance.
[0017] Optionally, the medium-coarse WC is recycled medium-coarse WC.
[0018] By adopting the above technical scheme, the regenerated medium-coarse WC can effectively reduce the overall cost of cemented carbide, and the addition of ultrafine-grained WC can improve the grain regularity of coarse-grained WC and regenerated medium-coarse WC, reduce the content of sharp particles in the alloy part, thereby reducing the generation of micro-abrasive particles and improving the wear resistance of the alloy part.
[0019] Optionally, the ultrafine-grained WC is ultrafine-grained WC dispersed and modified by a dispersant.
[0020] By adopting the above technical scheme, it is preferred to use a dispersant to disperse the ultrafine-grained WC, so that the ultrafine-grained WC can obtain a better dispersion effect during the wet grinding process, so that the ultrafine-grained WC can fully form a uniform grading effect in the alloy part, and then with the solid solution in the bonding phase, it is evenly distributed in the alloy part and the sharp parts of the coarse-grained WC grains are wrapped, thereby improving the density of the alloy part and the generation of micro-abrasive particles, so that the alloy part obtains excellent wear resistance and mechanical strength.
[0021] Optionally, the alloy portion is an alloy portion that has been subjected to plasma boriding treatment.
[0022] By adopting the above technical solution, after plasma treatment, the roughness of the surface of the alloy part can be increased, which is beneficial to improving the bonding strength between the alloy part and the coating.
[0023] Optionally, the coating is a diamond coating, and the diamond coating is a multi-layer composite structure, and the multi-layer composite structure includes a connecting layer, a supporting layer and a top layer.
[0024] By adopting the above technical solution, compared with a single-layer diamond coating, the multi-layer structure can improve the crack propagation resistance, toughness and plastic deformation resistance of the coating, so that the diamond coating can stably improve the wear resistance and mechanical strength of the cemented carbide. Since the alloy part is pre-treated with plasma boronization, the WC grain boundary can be blurred, and more adsorption sites are added for diamond nucleation. The CoWB passivation layer and W transition layer can reduce the diffusion and migration of Co, reduce its adverse effects on the diamond coating, and are conducive to the nucleation and growth of diamond, thereby obtaining a dense and uniform diamond coating.
[0025] Optionally, the top layer includes porous diamond, and the porous diamond is loaded with paraffin wax.
[0026] By adopting the above technical solution, porous diamond is preferably used to load the paraffin, so that the paraffin can gradually seep out to lubricate the coating, thereby reducing the friction coefficient of the coating surface, so that the cemented carbide obtains excellent wear resistance.
[0027] Optionally, the porous diamond is prepared as follows: diamond powder, paraffin wax, high-density polyethylene and stearic acid are mixed, fed, and sintered to obtain the porous diamond.
[0028] By adopting the above technical solution, the preparation method of porous diamond is optimized, so that the diamond surface can obtain more pore structures, which is conducive to carrying paraffin.
[0029] In a second aspect, the present application provides a method for preparing a wear-resistant hard alloy for a tamping pick, using the following technical solution:
[0030] A method for preparing a wear-resistant hard alloy for a tamping pick comprises the following steps:
[0031] S1. Preparation of alloy part: placing the hard phase and the binder phase in a ball mill for ball milling, drying, pressing and sintering to obtain the alloy part;
[0032] S2. Preparation of cemented carbide: A coating is deposited on the surface of the alloy part by a hot wire deposition method to prepare cemented carbide.
[0033] In summary, this application has the following beneficial effects:
[0034] 1. Since the present application adopts the introduction of Mo element, it can act as a growth inhibitor to inhibit the growth of WC grains, refine the grains in the alloy part, and make the bonding phase evenly distributed, thereby further enhancing the mechanical strength of the alloy part. The addition of Ru can accelerate the polycrystalline transformation of Co cubic crystal to hexagonal crystal, thereby generating a dispersed substructure in the alloy part, slightly refine the WC grains, reduce the transgranular fracture of abnormally grown WC grains during the failure process, and effectively improve the wear resistance and mechanical strength of cemented carbide.
[0035] At the same time, the present application optimizes the particle size of Ru. At an appropriate particle size, Ru can be evenly distributed, evenly improving the dislocation strain energy of the alloy part, and increasing the solid solubility of Ru in Co, thereby increasing the dispersion of Ru, thereby enabling the cemented carbide to obtain better mechanical strength.
[0036] 2. In the present application, coarse-grained WC, medium-coarse WC and ultrafine-grained WC are selected as the hard phase to form a grading effect in the hard phase. The addition of medium-coarse WC and ultrafine-grained WC can alleviate the abnormal growth of grains and reduce the generation of ultra-coarse grains; the fine-grained WC and ultrafine-grained WC dissolved from the medium-coarse WC can move with the bonding phase and be evenly distributed around the coarse-grained WC, effectively improving the adjacency of the alloy; in addition, the introduction of medium-coarse WC is not prone to cracking and breaking, reduces the generation of micro-abrasive particles, and can also serve as a skeleton structure in the alloy part to improve the skeleton strength in the alloy part, while maintaining the strength of the alloy part, effectively improving the wear resistance of the alloy part.
[0037] 3. The present application uses porous diamond to load the paraffin wax, so that the paraffin wax can gradually seep out to lubricate the coating, thereby reducing the friction coefficient of the coating surface, so that the cemented carbide obtains excellent wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a product schematic diagram of xky-q-1 mentioned in the background technology.
[0039] Explanation of the accompanying drawings: 1. ramming pick body; 2. positioning pin; 3. cemented carbide sheet. DETAILED DESCRIPTION
[0040] The present application is further described in detail below with reference to the embodiments.
[0041] Preparation Example
[0042] WC Preparation Example
[0043] Preparation Example 1
[0044] Coarse-grained WC, medium-coarse WC and ultrafine-grained WC are mixed in a mass ratio of 7:2:1 to obtain WC.
[0045] Among them, the particle size of coarse-grained WC is 11-13μm, the total carbon content is 6.13±0.05%, and the single carbon content is 0.05; O: 0.03. The particle size of medium-coarse WC is 2.3-2.7μm, the total carbon content is 6.13±0.05%, and the single carbon content is 0.05; O: 0.07. The particle size of ultrafine-grained WC is 200nm, the total carbon content is 6.13±0.05%, and the single carbon content is 0.05; O: 0.09.
[0046] Preparation Example 2
[0047] Coarse-grained WC, medium-coarse WC and ultrafine-grained WC are mixed in a mass ratio of 6:3:1 to obtain WC.
[0048] Among them, the particle size of coarse-grained WC is 11-13μm, the total carbon content is 6.13±0.05%, and the single carbon content is 0.05; O: 0.03. The particle size of medium-coarse WC is 2.3-2.7μm, the total carbon content is 6.13±0.05%, and the single carbon content is 0.05; O: 0.07. The particle size of ultrafine-grained WC is 200nm, the total carbon content is 6.13±0.05%, and the single carbon content is 0.05; O: 0.09.
[0049] Preparation Example 3
[0050] Coarse-grained WC, recycled medium-coarse WC and ultrafine-grained WC are mixed in a mass ratio of 7:2:1 to obtain WC.
[0051] Among them, the particle size of coarse grain WC is 11-13μm, the total carbon content is 6.13±0.05%, and the single carbon content is 0.05; O: 0.03. The particle size of regenerated medium coarse WC is 2.5μm, the total carbon content is 6.13±0.05%, and the single carbon content is 0.05; O: 0.18. The particle size of ultrafine grain WC is 200nm, the total carbon content is 6.13±0.05%, and the single carbon content is 0.05; O: 0.09.
[0052] Preparation Example 4
[0053] Coarse-grained WC, medium-coarse WC and ultrafine-grained WC dispersed and modified by a dispersant are mixed in a mass ratio of 7:2:1 to obtain WC.
[0054] Preparation of ultrafine WC: ultrafine crystal WC is placed in distilled water (solid-liquid ratio is 1:10), PEG-2000 (concentration is 10%) is added, ultrasonic treatment is performed, filtration is performed, solid matter is retained, drying is performed, and crushing is performed to obtain ultrafine WC dispersed by a dispersant.
[0055] Among them, the particle size of coarse-grained WC is 11-13μm, the total carbon content is 6.13±0.05%, and the single carbon content is 0.05; O: 0.03. The particle size of medium-coarse WC is 2.3-2.7μm, the total carbon content is 6.13±0.05%, and the single carbon content is 0.05; O: 0.07. The particle size of ultrafine-grained WC is 200nm, the total carbon content is 6.13±0.05%, and the single carbon content is 0.05; O: 0.09.
[0056] Preparation example of porous diamond
[0057] Preparation Example 5
[0058] Diamond powder and binder are mixed in a mass ratio of 4:6, fed, injection molded at 165°C, sintered at 1050°C, and crushed to obtain porous diamond. The porous diamond is immersed in paraffin, filtered, and dried to obtain porous diamond loaded with paraffin.
[0059] The binder includes 70% paraffin wax, 25% high density polyethylene and 5% stearic acid.
[0060] Example
[0061] Example 1
[0062] On the one hand, the present application provides a wear-resistant cemented carbide for a tamping pick, comprising an alloy portion and a coating disposed outside the alloy portion, wherein the alloy portion comprises 75 parts of a hard phase and 25 parts of a bonding phase.
[0063] Specifically, the hard phase is coarse-grained WC, and the binder phase includes 2 μm Ni, 1.5 μm Co, 1 μm Mo, and 1.5 μm Ru in a mass ratio of 2:6:0.5:0.2.
[0064] The coating is a diamond coating, and the diamond coating is a multi-layer composite structure.
[0065] On the other hand, the present application provides a method for preparing a wear-resistant cemented carbide for a tamping pick, comprising the following steps:
[0066] S1. Preparation of alloy part: disperse the hard phase and the binder phase in anhydrous ethanol, ultrasonically disperse for 1 hour, place in a ball mill for ball milling, use YG8 grinding balls, the mass ratio of grinding balls to slurry is 1:1, ball milling at 63 rpm for 16 hours, filter, dry, press, and sinter at 1450°C for 90 minutes to obtain the alloy part;
[0067] S2. Preparation of cemented carbide: A coating is deposited on the surface of the alloy part by a hot wire deposition method to prepare cemented carbide.
[0068] The alloy part is immersed in a micron diamond suspension (mass fraction is 1%), ultrasonically vibrated for 30 minutes, and then subjected to hot wire deposition treatment to obtain a pretreated alloy part;
[0069] In the hot wire deposition process, the hot wire is a spiral tungsten wire with a diameter of 0.5 mm, the horizontal distance between the two tungsten wires is 10 mm, and the vertical distance between the tungsten wire and the substrate is 7 mm. The diamond nucleation time is 1 hour, and the reaction gas is methane (CH 4 ) and hydrogen (H 2 ), the gas flow rates were 3 mL / min and 98 mL / min respectively, and the deposition pressure was 2 kPa.
[0070] The pretreated alloy part was immersed in a suspension (mass fraction of 1%) of micron diamond and β-SiC (mass ratio of 2:1), ultrasonically vibrated for 30 minutes, and then subjected to hot wire deposition treatment to obtain an alloy part with a connection layer deposited thereon; wherein, in the hot wire deposition treatment, the hot wire was a spiral tungsten Ta wire with a diameter of 0.5 mm, the horizontal distance between the two Ta wires was 10 mm, and the vertical distance between the Ta wire and the substrate was 7 mm. The diamond nucleation time was 1 hour, and the reaction gas was methane (CH 4 ), hydrogen (H 2 ) and tetramethylsilane (TMS), with gas flow rates of 3 mL / min, 98 mL / min and 20 mL / min respectively, and a deposition pressure of 5 kPa.
[0071] The alloy part with the connection layer deposited thereon is immersed in a micron diamond suspension (mass fraction of 1%), subjected to ultrasonic oscillation for 30 minutes, and then subjected to hot wire deposition treatment to obtain an alloy part with the support layer deposited thereon;
[0072] In the hot wire deposition process, the hot wire is a spiral tungsten wire with a diameter of 0.5 mm, the horizontal distance between the two tungsten wires is 10 mm, and the vertical distance between the tungsten wire and the substrate is 7 mm. The diamond nucleation time is 1 hour, and the reaction gas is methane (CH 4 ) and hydrogen (H 2 ), the gas flow rates were 3 mL / min and 98 mL / min respectively, and the deposition pressure was 2 kPa.
[0073] The alloy part with the support layer deposited thereon was immersed in a nano-diamond suspension (mass fraction of 1%), subjected to ultrasonic oscillation for 30 minutes, and then subjected to hot wire deposition treatment to obtain a cemented carbide.
[0074] In the hot wire deposition process, the hot wire is a spiral tungsten wire with a diameter of 0.5 mm, the horizontal distance between the two tungsten wires is 10 mm, and the vertical distance between the tungsten wire and the substrate is 7 mm. The diamond nucleation time is 1 hour, and the reaction gas is methane (CH 4 ) and hydrogen (H 2 ), the gas flow rates were 3 mL / min and 98 mL / min respectively, and the deposition pressure was 2 kPa.
[0075] Example 2
[0076] The difference from Example 1 is that the alloy portion includes 80 parts of hard phase and 20 parts of binder phase to prepare a cemented carbide.
[0077] Example 3
[0078] The difference from Example 1 is that the alloy portion includes 85 parts of hard phase and 15 parts of binder phase, and a cemented carbide is prepared.
[0079] Example 4
[0080] The difference from Example 3 is that an equal mass of WC prepared in Preparation Example 1 is used to replace the WC in Example 1 to prepare cemented carbide.
[0081] Example 5
[0082] The difference from Example 3 is that an equal mass of WC prepared in Preparation Example 2 is used to replace the WC in Example 1 to prepare cemented carbide.
[0083] Example 6
[0084] The difference from Example 3 is that an equal mass of WC prepared in Preparation Example 3 is used to replace the WC in Example 1 to prepare cemented carbide.
[0085] Example 7
[0086] The difference from Example 3 is that an equal mass of WC prepared in Preparation Example 4 is used to replace the WC in Example 1 to prepare cemented carbide.
[0087] Example 8
[0088] The difference from Example 3 is:
[0089] The alloy part with the support layer deposited thereon was immersed in the porous diamond suspension (mass fraction of 1%) prepared in Preparation Example 5, subjected to ultrasonic oscillation for 30 minutes, and then subjected to hot wire deposition treatment to obtain a cemented carbide.
[0090] In the hot wire deposition process, the hot wire is a spiral tungsten wire with a diameter of 0.5 mm, the horizontal distance between the two tungsten wires is 10 mm, and the vertical distance between the tungsten wire and the substrate is 7 mm. The diamond nucleation time is 1 hour, and the reaction gas is methane (CH 4 ) and hydrogen (H 2 ), the gas flow rates were 3 mL / min and 98 mL / min respectively, and the deposition pressure was 2 kPa.
[0091] Example 9
[0092] The difference from Example 3 is: S1. Preparation of the alloy part: disperse the hard phase and the binding phase in anhydrous ethanol, ultrasonically disperse for 1 hour, place in a ball mill for ball milling, YG8 grinding balls, the mass ratio of grinding balls to slurry is 1:1, ball milling at 63rpm for 16 hours, filter, dry, press, sinter at 1450℃ for 90 minutes to obtain the alloy part, and perform plasma boronizing treatment on the alloy part.
[0093] Plasma boriding treatment is as follows:
[0094] The surface of the dried cemented carbide was etched by generating plasma using a tube furnace equipped with a radio frequency power supply. Argon (Ar) and diborane (5% B 2 H 6 +95%H 2 (mass fraction)), the gas flow rates are 30 mL / min and 10 mL / min respectively, the gas pressure is about 10 Pa, the output power is 300 W, the chamber temperature is 1000 ° C, and the etching time is 60 min.
[0095] Comparative Example
[0096] Comparative Example 1
[0097] The difference between this comparative example and Example 3 is that in this comparative example, Ru and Mo are not added to the binder phase.
[0098] Comparative Example 2
[0099] The difference between this comparative example and Example 3 is that the diamond coating in this comparative example is a micron diamond coating.
[0100] Performance testing
[0101] (1) Wear resistance test: The wear performance of the sample (1 / mm) was tested using the ASTM B611 abrasive wear test standard. 3 ), test the wear resistance coefficient of the alloy part and the cemented carbide.
[0102] (2) Hardness test: The hardness of the alloy part and the cemented carbide was measured at room temperature using a LHBRV-187.5DX Vickers hardness tester.
[0103] (3) Fracture toughness test: The fracture toughness of the alloy was tested using a PWS-100 / V3.0 electronic universal testing machine using the V-notch method.
[0104] (4) Elastic modulus test: Use a nanoindentation tester to test the hardness and elastic modulus of cemented carbide.
[0105] Table 1 Alloy performance test
[0106]
[0107]
[0108] Table 2 Cemented carbide performance test
[0109]
[0110] Combining the performance test comparison of Table 1 and Table 2, we can find that:
[0111] 1. By comparing Examples 1-3 with Comparative Example 1, it can be found that the hardness, fracture toughness and wear resistance of the alloy parts and cemented carbides prepared in Examples 1-3 are all improved, which shows that the addition of Ru in the present application can accelerate the polycrystalline transformation of Co cubic crystal to hexagonal crystal, thereby generating a dispersed substructure in the alloy part, slightly refining the WC grains, reducing the transgranular fracture of abnormally grown WC grains during the failure process, and effectively improving the wear resistance and mechanical strength of the cemented carbide. At the same time, the present application optimizes the particle size of Ru. At a suitable particle size, Ru can be evenly distributed, uniformly improving the dislocation strain energy of the alloy part, and increasing the solid solubility of Ru in Co, thereby increasing the dispersion of Ru, and thus enabling the cemented carbide to obtain better mechanical strength.
[0112] 2. By comparing Examples 4-6 with Example 3, it can be found that the hardness, fracture toughness and wear resistance of the alloy parts obtained in Examples 4-6 are all improved, which means that coarse-grained WC, medium-coarse WC and ultrafine-grained WC are selected as the hard phase in the present application to form a grading effect in the hard phase. The addition of medium-coarse WC and ultrafine-grained WC can alleviate the abnormal growth of grains and reduce the generation of ultra-coarse grains. The fine-grained WC and ultrafine-grained WC dissolved from the medium-coarse WC are evenly distributed around the coarse-grained WC, improving the adjacency of the alloy. In addition, the medium-coarse WC is not prone to cracking and breaking, reducing the generation of micro-abrasive particles, and serves as a skeleton structure in the alloy part to improve the skeleton strength in the alloy part.
[0113] 3. By comparing Example 7 with Example 3, it can be found that the hardness, fracture toughness and wear resistance of the alloy part obtained in Example 7 are all improved, which means that the dispersant is used in the present application to disperse the ultrafine-grained WC, so that the ultrafine-grained WC can obtain a better dispersion effect during the wet grinding process, so that the ultrafine-grained WC can fully form a uniform grading effect in the alloy part, and then with the solid solution in the bonding phase, it is evenly distributed in the alloy part and the sharp parts of the coarse-grained WC grains are wrapped, thereby improving the density of the alloy part and the generation of micro-abrasive particles, so that the alloy part obtains excellent wear resistance and mechanical strength.
[0114] 4. By comparing Example 3, Example 8 and Comparative Example 2, it can be found that the hardness, fracture toughness and wear resistance of the cemented carbide prepared in Example 8 are all improved, which means that compared with the single-layer diamond coating in the present application, the setting of the diamond and silicon carbide connecting layer can play a blocking role for cracks that initiate and extend upward in the cobalt-poor layer, and then the setting of the multi-layer structure can improve the crack propagation resistance, toughness and plastic deformation resistance of the coating, so that the diamond coating can stably improve the wear resistance and mechanical strength of the cemented carbide.
[0115] 5. By comparing Example 9 with Example 3, it can be found that the hardness, fracture toughness and wear resistance of the cemented carbide prepared in Example 9 are improved, which means that porous diamond is used to load the paraffin wax in the present application, and then the paraffin wax can gradually seep out to lubricate the coating, thereby reducing the friction coefficient of the coating surface, so that the cemented carbide obtains excellent wear resistance.
[0116] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A wear-resistant hard alloy for a tamping pick, characterized in that: The invention comprises an alloy part and a coating arranged outside the alloy part, wherein the alloy part comprises the following substances in parts by weight: 75-95 parts of hard phase; 5-25 parts of adhesive phase; The hard phase includes WC; The bonding phase includes any one or more of Ni, Co, Mo, and Ru; the particle size of Ru is 1-2 μm.
2. The wear-resistant hard alloy for tamping pick according to claim 1, characterized in that: The WC includes coarse-grained WC, medium-coarse WC and ultrafine-grained WC.
3. A wear-resistant hard alloy for a tamping pick according to claim 2, characterized in that: The WC includes coarse-grained WC, medium-coarse WC and ultrafine-grained WC in a mass ratio of 6-7:2-3:
1.
4. The wear-resistant hard alloy for tamping pick according to claim 2, characterized in that: The medium-coarse WC is recycled medium-coarse WC.
5. The wear-resistant hard alloy for tamping pick according to claim 2, characterized in that: The ultrafine-grained WC is ultrafine-grained WC that has been dispersed and modified by a dispersant.
6. The wear-resistant hard alloy for tamping pick according to claim 4, characterized in that: The alloy portion is an alloy portion that has been subjected to plasma boronizing treatment.
7. The wear-resistant hard alloy for tamping pick according to claim 1, characterized in that: The coating is a diamond coating, which is a multi-layer composite structure. The multi-layer composite structure includes a connecting layer, a supporting layer and a top layer.
8. The wear-resistant hard alloy for tamping pick according to claim 7, characterized in that: The top layer includes porous diamond, and the porous diamond is loaded with paraffin wax.
9. The wear-resistant hard alloy for a tamping pick according to claim 8, characterized in that: The porous diamond is prepared as follows: diamond powder, paraffin wax, high-density polyethylene and stearic acid are mixed, fed, and sintered to obtain the porous diamond.
10. A method for preparing a wear-resistant hard alloy for a tamping pick according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Preparation of alloy part: placing the hard phase and the binder phase in a ball mill for ball milling, drying, pressing and sintering to obtain the alloy part; S2. Preparation of cemented carbide: A coating is deposited on the surface of the alloy part by a hot wire deposition method to prepare cemented carbide.
Citation Information
Patent Citations
WC-based hard alloy material based on high-entropy alloy and preparing method of WC-based hard alloy material
CN108950343A
Application of high-entropy alloy and preparation method thereof
CN109295373A
Polycrystalline diamond composite compact elements and methods of making and using same
US20140311810A1